Аналіз загальних настанов щодо оцінювання токсичності летких продуктів горіння полімерної продукції - Шафран, Л.М.; Новак, С.В.; Кравченко, Р.І.; Леонова, Д.І. (Актуальні проблеми транспортної медицини, 2009)
Проведен анализ основных положений международной нормативно методической документации, определяющей требования к проведению испытаний полимерных материалов и полимерсо держащей продукции на токсичность продуктов горения в системе пожаробезопасности и сохранения здоровья населения. Показано, что они охватывают обширную сферу вопросов, касающихся гигиены, токсикологии и безопасного применения полимеров в условиях повышенной пожароопасности. Вместе с тем, ряд положений этих документов дискутабелен, а многие требуют дальнейших целенаправленных исследований для решениия теоретических и прикладных задач гигиены, токсикологии и безопасного применения полимеров. The analysis of substantive provisions of the international standards and methodical documentation defining the requirements to carrying out of tests of polymeric materials and polymercontaining production on the combustive products toxicity in system of fire safety and population health prophylaxis is carried out. It is shown, that they cover extensive sphere of the questions, concerning hygiene, toxicology and safe application of polymers in the conditions of the raised fire danger. At the same time, a number of positions of these documents is under disscution, and many demand the further purposeful researches for solving theoretical and applied problems of hygiene, toxicology and safe application of polymers.